Exploring the Sources of Academic Stress and Adopted Coping Mechanisms among University Students - Islam, Md. Sefatul; Rabbi, Md. Fajlay (International Journal on Studies in Education, 2024)
The primary objective of this research is to find out the origins of academic stress and the coping strategies employed by university going students. This research seeks to the find out the sources and causes of academic stress and explore the coping mechanisms adopted by students. This study utilizes a qualitative methodology. Thirty university students have undergone in-depth interviews (IDI). The data has undergone thematic analysis. Research findings uncover the various sources and underlying causes of academic stress among university students such as test anxiety, overloads of assignment, standards established by peers, lack of library resources, health issues during class tests and term final exams, virtual group discussions and works, unexpected course difficulty, clashes of deadline, difficulty regarding research proposal, lack of clarity in feedback. The study identifies and analyze coping strategies such as planning and prioritizing, study breaks, mindfulness and deep breathing, setting realistic goals healthy lifestyle choices, utilizing university resources use of time management apps and hobbies. The results are anticipated to provide valuable knowledge to both the academic community and student support services, assisting in the creation of focused interventions to tackle academic stressors and improve students' overall well-being. The primary objective is to establish a nurturing educational setting that promotes resilience and provides students with efficient techniques to effectively handle the difficulties encountered in higher education.